Colorado cytospora canker complex on Populus tremuloides Michx. - Kepley, Jeff B., author; Reeves, F. Brent, advisor (Colorado State University. Libraries, 2009)
Cytospora canker is a serious fungal disease affecting aspen in natural and commercial forests as well as urban sites. In Colorado the causal organism responsible for this canker disease is typically reported to be Cytospora chrysosperma (Pers.) Fr. However, a thorough understanding of the species of Cytospora attacking aspen in Colorado is lacking. Fungal identification has been based upon morphological characteristics of fruiting/vegetative structures despite the plasticity known to occur in such diagnostic features. Examinations of cankers on aspen stems in Colorado revealed a morphologically distinct Cytospora-like fungus that frequently co-occurs with C. chrysosperma. This fungus is a new species and is closely associated with and superficially resembles C. chrysosperma. Based on these findings Cytospora canker on aspen in Colorado is a complex of fungi, contrary to what is typically reported in the literature. Isoenzyme analysis was employed as an initial step to determine the genetic/biochemical differences that occur among and between C. chrysosperma and the new non-C. chrysosperma isolates. Of the twelve enzyme systems initially screened only three, viz., alpha esterase, amylase, and glucose-6-phosphate dehydrogenase, provided good resolution for all isolates. Following cluster analysis, two major clades well-delineated the two taxa. Phylogenetic analyses of ITS1-5.8S-ITS2 rDNA and EF-1α sequences produced phylogenetic trees in which non- C. chrysosperma isolates formed a monophyletic clade (with strong bootstrap support and high posterior probability) within a Cytospora spp. phylogeny. Based on these results the non-C. chrysosperma isolates from aspen in Colorado are considered a new Cytospora species. External morphological features of the ascostromata and conidiomata (natural specimens) as well as histological sections of the new Cytospora sp. reveal conceptacles and conceptacle-like tissues which gives fruit bodies a unique target-like appearance. Cultures are darkly pigmented and display robust (large diameter) bead-like hyphae; many hyphal tips from young cultures lyse. Pycnidia produced in vitro do not enclose a multi-lobed locular structure; rather they have indentations/pockets with conidiophores lining these invaginations as well as pycnidial surfaces. In addition to the Cytospora anamorph a Phialocephala-like synanamorph is produced by some isolates. Descriptions of the new Cytospora species and C. chrysosperma, occurring on aspen in Colorado, are provided.
Keywords: Cytospora canker; Populus tremuloides; molecular biology; plant biology; forestry; plant sciences; botany; plant pathology